Modelling of atmospheric mid-infrared radiative transfer: the AMIL2DA algorithm intercomparison experiment - von Clarmann, T; Hopfner, M; Funke, B; Lopez-Puertas, M; Dudhia, A; Jay, V; Schreier, F; Ridolfi, M; Ceccherini, S; Kerridge, B; Reburn, J; Siddans, R (2003)
When retrieving atmospheric parameters from radiance spectra, the forward modelling of radiative transfer through the Earth's atmosphere plays a key role, since inappropriate modelling directly maps on to the retrieved state parameters. In the context of pre-launch activities of the Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) experiment, which is a high resolution limb emission sounder for measurement of atmospheric composition and temperature, five scientific groups intercompared their forward models within the framework of the Advanced MIPAS Level 2 Data Analysis (AMIL2DA) project. These forward models have been developed, or, in certain respects, adapted in order to be used as part of the groups' MIPAS data processing. The following functionalities have been assessed: the calculation of line strengths including non-local thermodynamic equilibrium, the evaluation of the spectral line shape, application of chi-factors and semi-empirical continua, the interpolation of pre-tabulated absorption cross sections in pressure and temperature, line coupling, atmospheric ray tracing, the integration of the radiative transfer equation through an inhomogeneous atmosphere, the convolution of monochromatic spectra with an instrument line shape function, and the integration of the incoming radiances over the instrument field of view. © 2003 Elsevier Science Ltd. All rights reserved.